PHYTOCHEMICAL ANALYSIS, ANTIMICROBIAL SCREENING AND ANTIHELMINTHIC PROPERTIES OF Phyllanthus emblica - SUKANYA M.K; SHIMI SUKU; ARUNA .S.R. (International Journal of Pharma and Bio Sciences, 2013)
In our study, preliminary phytochemical analysis, antimicrobial and antihelminthic investigation on Phyllanthus emblica was done. P.emblica is a well known and an important medicinally valued plant. Although the efficacy of P.emblica fruit is widely proved, use of leaf and bark is less investigated. Present aim of our study is to find the biologically active compound present in this particular plant, check its antimicrobial and antihelminthic property. Different solvent extract of the leaf and bark were used to identify the bioactive compounds present and its antimicrobial activity was checked against different human pathogens(MTCC).Antihelminthic activty was checked against Phertima posthuma. The study shown it has promising antimicrobial and antihelminthic property. Methanol of the leaf sample showed highest zone of inhibition against Enterobacter aerogens and Enterobacter feacalis. Ethyl acetate of leaf and bark sample showed antifungal activity against Rhizomucor species.The pharmacological property of this medicinally important plant has to be further investigated.